2020
DOI: 10.1186/s12885-020-07536-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating immune cells (TIICs) as a biomarker for prognosis benefits in patients with osteosarcoma

Abstract: Background Osteosarcoma is a rare malignant bone tumor in adolescents and children. Poor prognosis has always been a difficult problem for patients with osteosarcoma. Recent studies have shown that tumor infiltrating immune cells (TIICs) are associated with the clinical outcome of osteosarcoma patients. The aim of our research was to construct a risk score model based on TIICs to predict the prognosis of patients with osteosarcoma. Methods CIBERSORTX algorithm was used to calculate the proportion of 22 TIIC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Reports have indicated that infiltrating immune cells in the TME are accompanied by cancer development ( Zalocusky et al, 2018 ). Infiltrating immune cells are used as biomarkers for the immunotherapy response in many cancers ( Chen et al, 2020 ). However, the function of every type of infiltrating immune cell in cancer development and the underlying mechanism still need further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…Reports have indicated that infiltrating immune cells in the TME are accompanied by cancer development ( Zalocusky et al, 2018 ). Infiltrating immune cells are used as biomarkers for the immunotherapy response in many cancers ( Chen et al, 2020 ). However, the function of every type of infiltrating immune cell in cancer development and the underlying mechanism still need further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…Gomez-Brouchet et al found that CD8 T cells were related to the non-metastatic osteosarcoma [88], and higher infiltration rate of CD8 T cells indicated improved survival outcome [89], showing consistency with our result that the low-risk osteosarcoma patients with superior prognosis had higher infiltration proportion of CD8 T cells. In terms of activated dendritic cells, Wang et al demonstrated that activated dendritic cell was an independent predictor of osteosarcoma and the model basing on several immune cell types including activated dendritic cell could reliably predict the prognosis of osteosarcoma patients [90], suggesting the potentially important role of activated dendritic cells in osteosarcoma. However, the specific functions of these significantly distinct infiltrating immune cells between the osteosarcoma patients with high and low risk scores and the underlying mechanism still need further research.…”
Section: Discussionmentioning
confidence: 99%
“…Another hint was the identification of similar inflammatory and tissue remodeling mechanisms that are shared between tumor stroma formation and wound healing processes, which have led to the concept that tumors are “wounds that do not heal” [ 11 , 12 ]. It is now well-established that tumor-infiltrating immune cells can predict survival and therapeutic outcomes in several malignancies such as osteosarcoma, colorectal, or breast cancer (BrCa) [ 13 , 14 , 15 , 16 ]. An additional level of complexity is added by the presence of other resident cells and structures within the tumor microenvironment (TME), which are not silent bystanders but are rather fostered (or at least affected) by inflammatory mechanisms, including tumor-associated macrophages (TAM) [ 17 ], cancer-associated fibroblasts (CAFs) [ 18 ], mesenchymal stromal cells [ 19 ], adipocytes [ 20 ], and endothelial cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%